Development of sulfonated polysulfone membranes as a material for Proton Exchange Membrane (PEM) - Naim, R.; Ismail, A. F.; Saidi, H.; Saion, E. (2004)
This paper reports the development of sulfonated polysulfone (SPSU) membrane as potential candidates for proton exchange membrane through sulfonation process. Sulfonated polysulfone membranes have been prepared by conducting sulfonation reaction at room temperature with a mild sulfonating agent, trimethylsilyl chlorosulfonate (TMSCS). The membranes were sulfonated with different molar ratio of sulfonating agent to the polymer repeat unit. The degree of sulfonation was determined by elemental analysis and Fourier Transform Infrared (FTIR) was performed to verify the sulfonation reaction on the polysulfone polymer. The sulfonated polysulfone membranes have been characterized by ion exchange capacity (IEC), water uptake and proton conductivity as a function of molar ratio and degree of sulfonation. It was shown that increases in the molar ratio of the sulfonating agent to polysulfone repeat unit lead to an increasing degree of sulfonation. The water uptake of the sulfonated polysulfone membrane was increased with an increase in degree of sulfonation from 4.1 wt.% up to 26 wt.% with the value of IEC about 0.62 mmol/g and 1.78 mmol/g respectively. Area resistance of the sulfonated membranes were decreases as a function of temperature and degree of sulfonation. The conductivity values in the range of 10-4 –10-3 S/cm were obtained for SPSU membranes. The conductivity of the membranes show similar increasing trend as a function of operating temperature.